Using Mistake Buster Technique to Improve the Recount Text Writing Skill of the Eighth Graders of MTS Negeri Windusari in the School Year 2018/2019. - Setiya Andriyani (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2020)
Writing is one of the four language skills and very important in language learning. The eighth graders of MTs Negeri Windusari in the school year 2018/2019 are ones of those who face some difficulties in writing recount text. Mistake Buster is offered as a technique to improve their learning motivation and skill in writing recount text. The objectives of this research are to know whether the use of Mistake Buster technique can increase the recount text writing learning motivation of the eighth graders and to know how great the improvement of the recount text writing skill of the eighth graders who are taught by using Mistake Buster technique is.The writer did the research through three phases; they are Pre- Cycle, Cycle 1, and Cycle 2. The data of this research are collected from the students’ written test, questionnaire, observation, and documentation. All the data are analyzed using both qualitative and quantitative data analysis technique. The result of research shows that Mistake Buster technique give great improvement on the students’ learning motivation and skill in writing recount text.